2021
DOI: 10.1017/s0266467421000225
|View full text |Cite
|
Sign up to set email alerts
|

Roller dung beetles of dung piles suggest habitats are alike, but that of guarding pitfall traps suggest habitats are different

Abstract: Roller dung beetles play a pivotal role in the nutrient distribution in soil and secondary dispersal of seeds. Dung beetles are sampled either using a dung-baited pitfall trap or an exposed dung pile on the ground. While the former method is useful for a rapid survey of dung beetles, information on the ecology and behaviour of dung beetles can be lost, which the latter method provides, but underestimates species diversity due to its inefficiency in trapping rollers. Efficiency of a new method for sampling roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Regardless of the locations, the sacred groves contain relics of evergreen forests of the size < 10 ha. While the floristic aspects of the biodiversity of the sacred groves of these States are well-known 36,37 , with our investigations, the faunistic aspects of the biodiversity of the sacred groves are just coming to the light 30,31,34,[38][39][40] . While the sacred groves of Kodagu are located on a land mosaic of human settlements, business districts, homeyards, coffee plantations, and protected forests, the sacred groves of Kasaragod and Trivandrum are located on a land matrix of human settlements, business districts, and Coconut-based orchards or homeyards.…”
Section: Sacred Grovesmentioning
confidence: 60%
“…Regardless of the locations, the sacred groves contain relics of evergreen forests of the size < 10 ha. While the floristic aspects of the biodiversity of the sacred groves of these States are well-known 36,37 , with our investigations, the faunistic aspects of the biodiversity of the sacred groves are just coming to the light 30,31,34,[38][39][40] . While the sacred groves of Kodagu are located on a land mosaic of human settlements, business districts, homeyards, coffee plantations, and protected forests, the sacred groves of Kasaragod and Trivandrum are located on a land matrix of human settlements, business districts, and Coconut-based orchards or homeyards.…”
Section: Sacred Grovesmentioning
confidence: 60%
“…We used two dung piles consisting of 1000 g of cow dung each for sampling beetles from each habitat. Dung piles were laid on bare ground after clearing leaf litter, and kept undisturbed for 24 h. Although our research 46 showed that guarding pitfall traps around dung piles improve catches of roller dung beetles in protected forests, in sacred groves and home gardens they hardly collected rollers, suggesting that rollers may be less prevalent in fragments and used lands. The dung pile along with one-foot soil were retrieved and soaked in a bucket full of water and allowed the trapped beetles to float on the water.…”
Section: Methodsmentioning
confidence: 67%
“…Furthermore, carabid beetles display diurnal or nocturnal activity patterns in lowland and alpine areas depending on their species characteristics, habitat type, and ground surface temperature [23]. Daytime factors, soil surface temperature, season, locality [64], fragmentation, and land-use changes [65] have also been reported to affect the diurnal activity of ground-dwelling beetles in forests and clear-cut areas. Therefore, soil parameters, season, habitat, and land use should be considered to understand the hourly dynamics of ground-dwelling beetles in farmlands.…”
Section: Hourly Dynamics Of Abundance In Each Taxonmentioning
confidence: 99%